2020
DOI: 10.1177/1557988320970053
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species Secreted by Leukocytes in Semen Induce Self-Expression of Interleukin-6 and Affect Sperm Quality

Abstract: Reproductive tract inflammation is considered an important cause of male infertility. Increased leukocytes in semen can produce many reactive oxygen species (ROS), which affect sperm function. The aim of this study is to identify the main source of ROS in seminal plasma and to assess the effect of ROS on leukocytes. Semen samples ( n = 20) with leukocyte concentration >1 × 106 were collected from a male infertility clinic. This study mainly compares the sperm function parameters of the normal group and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 40 publications
(42 reference statements)
0
25
0
Order By: Relevance
“…Interleukin-8 (IL-8) has been found to correlate with sperm DNA damage and sperm vitality in certain studies, but no other cytokine [ 16 ]. Alternatively, other studies found significantly increased levels of IL-2, IL-4, IL-6, IFN-γ, and, particularly, TNF-α in human semen in association with leukocytospermia [ 17 , 18 , 19 , 20 ]. These, and other seminal cytokine-like molecules such as resistin [ 21 ], are clearly indicative of a proinflammatory state and are intimately associated with the induction of leucocyte infiltration; however, there is little evidence to suggest that cytokines are directly responsible for any changes in sperm functionality [ 22 ].…”
Section: Sources Of Ros In the Human Ejaculatementioning
confidence: 99%
“…Interleukin-8 (IL-8) has been found to correlate with sperm DNA damage and sperm vitality in certain studies, but no other cytokine [ 16 ]. Alternatively, other studies found significantly increased levels of IL-2, IL-4, IL-6, IFN-γ, and, particularly, TNF-α in human semen in association with leukocytospermia [ 17 , 18 , 19 , 20 ]. These, and other seminal cytokine-like molecules such as resistin [ 21 ], are clearly indicative of a proinflammatory state and are intimately associated with the induction of leucocyte infiltration; however, there is little evidence to suggest that cytokines are directly responsible for any changes in sperm functionality [ 22 ].…”
Section: Sources Of Ros In the Human Ejaculatementioning
confidence: 99%
“…The pathophysiology may be initiated by an increase in reactive oxygen species (ROS). 3 At a higher level, ROS may lead to oxidative stress and disrupt sperm physiology. Lipid peroxidation of the plasma membrane has been recognized as the mechanism of sperm damage in oxidative stress conditions.…”
Section: Discussionmentioning
confidence: 99%
“…2 Leukocytes are the source of Reactive Oxygen Species (ROS), leading to oxidative stress conditions and sperm damage. 3 Therefore, the association between leukocytospermia, poor semen quality, and infertility has been hypothesized, but it is still not clear to date. Lackner JE et al reported a positive association between leukocytes concentration and sperm motility and morphology, and the association might be concentrationdependent.…”
Section: Introductionmentioning
confidence: 99%
“…The ready detection of cytokines in seminal plasma has made them an attractive target to evaluate their potential association with male fertility status [ 93 , 97 , 98 ] and more recently, seminal ROS concentration [ 99 ]. Indeed, several studies have reported a positive relationship between the presence of leucocytes in semen and ROS production [ 100 ], while the latter has also positively correlated with the abundance of seminal plasma pro-inflammatory cytokines such as C-X-C motif chemokine ligand 8 (CXCL8) [ 99 , 101 ], interleukin 6 (IL6) [ 99 , 102 ] and tumor necrosis factor (TNF) [ 99 , 103 ]. CXCL8 has also been reported as being elevated in the seminal plasma of men with genitourinary tract infection [ 93 , 104 ] where it is believed associated with reduced fertility [ 105 , 106 ].…”
Section: Why We Are Still Likely Some Time Away From Semen Ros Measur...mentioning
confidence: 99%